Transformasi Pembiayaan KPR: Kolaborasi Bank, Developer, dan Fintech dalam Meningkatkan Akses Pembiayaan Perumahan di Era Digital - Putra Firdaus (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The growing demand for housing in urban areas has not been matched by equitable access to mortgage financing (Kredit Pemilikan Rumah/KPR), particularly for low- and middle-income households. Conventional bank-based mortgage schemes often face limitations related to risk management, administrative complexity, and funding capacity. This study aims to analyze how collaboration among banks, housing developers, and financial technology (FinTech) platforms can enhance access to housing finance in the digital era. Using a Systematic Literature Review (SLR) approach, this research synthesizes findings from 10 peer-reviewed journal articles selected through a rigorous screening process across major academic databases. The analysis focuses on collaboration models, regulatory compliance, risk mitigation mechanisms, and the role of digital innovation in mortgage financing. The results indicate that strategic collaboration between banks and developers, supported by FinTech solutions such as digital onboarding and alternative funding mechanisms, improves efficiency, transparency, and financial inclusion in housing finance. However, challenges remain in terms of legal certainty, data security, and infrastructure readiness. This study contributes by proposing an integrated digital housing finance ecosystem that aligns institutional collaboration with technological innovation, offering both theoretical insights and practical implications for policymakers and industry stakeholders.